Comprehensive geriatric assessment: Valuation and patient preferences in older Japanese adults with cancer. Issue 1 (16th September 2022) - Nishijima, Tomohiro F.; Shimokawa, Mototsugu; Esaki, Taito; Morita, Masaru; Toh, Yasushi; Muss, Hyman B.
Abstract: Background: Current guidelines recommend a comprehensive geriatric assessment (CGA) for the management of older adults with cancer. We evaluated the effect of CGA conducted by a geriatric oncology service (GOS) on the management of older adults with cancer. We also queried patients about their perceptions of the value of this process. Methods: This was a prospective quality assessment study of 498 consecutive older adults with cancer who were referred to the GOS from May 2020 through December 2021. Treating physicians requested a consultation and the GOS conducted a CGA and assessed patient preferences. The GOS provided recommendations on cancer treatment and geriatric interventions. Patient perspectives on the consultation were evaluated using collaboRATE and modified Patient Assessment of Care for Chronic Conditions (PACIC) subscales. Results: A 10‐item frailty index based on a CGA (FI‐CGA‐10) [Oncologist, 26, e1751 (2021)] in the 498 patients showed that 19% of patients were fit, 40% pre‐frail, and 41% frail. Prior to CGA the intent of the proposed cancer treatment was curative in 56% ( n = 280), life‐extending in 40% ( n = 201), and palliative in 3.4% ( n = 17). After a CGA consultation, a cancer treatment decision was changed in 45% of patients. The intent of treatment after the CGA consultation was curative in 45%, life‐extending in 34%, and palliative in 21%. At least one referral to relevant disciplines was recommended for 88% of patients and was implemented in 43%. As part of the GOS consultation educational support was provided to 97% of patients. Based on the collaboRATE and PACIC tools, patients perceived the GOS consultation positively and helpful for facilitating shared decision‐making and patient‐centered care. Conclusion: Our institutional experience demonstrated the valuable effect of the CGA consultation on oncologic decision‐making and geriatric interventions in a patient‐centered manner. Abstract : See related Editorial by Fernandes Dos Santos Hughes et al . in this issue.